Podologia aplicada em bovinos - VIEIRA, Laércio Remualdo; SOUZA, Pedro Augusto Momberg de (053, 2024)
A podologia bovina é a pratica que cuida da saúde dos cascos dos bovinos e fundamental para o bem-estar e desempenho dos animais. É uma técnica essencial dentro dessa área, que consiste na apara corretiva das extremidades dos cascos dos bovinos para evitar e ou reparar problemas de crescimento anormal, prevenir lesões e melhorar a mobilidade e a produtividade dos animais. Os cascos dos bovinos, quando não cuidados adequadamente, podem desenvolver uma série de problemas, como, infecções, desgastes e até deformidades que afetam a locomoção do animal e sua saúde geral, principalmente os bovinos leiteiros, devido a alteração dos sistemas de produção, que estão preconizando o confinamento dos mesmos. . Além disso, proporciona a redução do desconforto e aumento da produtividade, visto que bovinos com cascos saudáveis apresentam melhor desempenho na produção, reprodução e bem-estar. Portanto, com a prática regular do casqueamento, o produtor melhora suas condições de produção e consequentemente sua produtividade.

Animal welfare is an interdisciplinary area that seeks to identify and meet the needs of animals, both in physical and psychological and behavioral aspects, with the aim of improving their quality of life. In the context of dairy production, the welfare of cattle is crucial, as well-treated and comfortable animals are better able to express their genetic potential, resulting in better quality milk production. This not only ensures consumer satisfaction, but also contributes to the profitability of the producer, who is able to obtain greater productivity and quality in his product. This concept is based on the "Five Pillars" of animal welfare defined by John Webster, which involves ensuring that animals are free from thirst, hunger and malnutrition, without pain, harm or disease, in a comfortable and suitable environment, with freedom to express their natural behavior, and without fear or stress. To assess the welfare of dairy cattle, several physiological and behavioral indicators are used, to identify it in a more practical way. Furthermore, the environment in which the animals are kept, such as the waiting pen and the ordering room, are extremely important to reduce stress and ensure the animals' comfort. These facilities have good ventilation, shade and are properly cleaned, to prevent diseases and improve the animal's experience before and after ordering. The relationship between humans and animals is also an important factor in well-being, as negative interactions can generate stress and affect milk production. Therefore, the quality of management and the behavior of managers have a direct impact on the health of the animals and, consequently, on their productivity. Finally, adequate nutritional management and constant veterinary care are essential to ensure that cattle are healthy and productive, thus ensuring that they produce good quality milk for consumers.
Keywords: Bovinos leiteiros; Bem-estar do animal; Bovinos leiteiros - manejo; Recursos Naturais